PENGARUH PARTISIPASI PENDIDIK DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI MA SEJAHTERA PARE - Nadiah, Nadiah; Ulfah, Maria; Salsabil, Putri; Rahma Suci Mulya, Dhya; Ahda Fadhla, Diva; Kholidatun Najah, Siti; Denni Chandra, Muhammad; Sigit Magistrianto, Rahman (STAI Bani Saleh, 2023)
Educators have a very close relationship with students in the learning process in class. In learning in the classroom the educator is the party who can supervise all student activities, thus the character of students can be formed with the participation of educators in learning. This study aims to determine whether or not there is an influence of educator participation in shaping the character of students in MA Sejahtera Pare. The method used in this study is correlation with a quantitative approach, sampling is done with the slovin formula using the Accidental Sampling method, with a total of 35 students as respondents. Data collection techniques with questionnaires and interviews. The results of the study show that there is an influence of educator participation in shaping the character of students, seen from the Product Moment coefficient test it produces